Clinical Trial of Allogeneic Mesenchymal Stem Cell Therapy for Chronic Active Antibody-Mediated Rejection in Kidney Transplant Recipients Unresponsive to Rituximab and Intravenous Immunoglobulin - Tae Hyun Ban; Sua Lee; Hyung Duk Kim; Eun Jeong Ko; Bo-Mi Kim; Kyoung-Woon Kim; Byung Ha Chung; Chul Woo Yang (Hindawi Limited, 2021)
Clinical trials of biologic agents for chronic active antibody-mediated rejection (CAMR) in kidney transplant recipients (KTRs) have been disappointing. We performed a clinical trial of mesenchymal stem cell (MSC) treatment in KTRs with CAMR unresponsive to rituximab and intravenous immunoglobulin. This study was a phase 1 clinical trial to confirm patient safety. Two patients with CAMR unresponsive to rituximab and intravenous immunoglobulin were included. Each patient received allogeneic MSCs for 4 cycles (1×106 cells/kg every other week) via the peripheral vein in the distal arm. We observed adverse events and renal function for 6 months after the final MSC infusion and analyzed changes in immunomodulatory parameters in the peripheral blood between the start of treatment and 3 months after the final MSC infusion. There were no serious adverse events during the study period. Renal function was stable during MSC treatment but gradually decreased between the final MSC infusion and the study endpoint (patient 1: creatinine levels ranged from 3.01 mg/dL to 7.81 mg/dL, patient 2: 2.87 mg/dL to 3.91 mg/dL). In peripheral blood sample analysis between the start of treatment and 3 months after the final MSC infusion, there were similar trends for immunomodulatory markers. Our study showed that there were no serious adverse events for six months after allogeneic MSC treatment in KTRs with CAMR refractory to rituximab and intravenous immunoglobulin, but further studies need to define the efficacy of MSC treatment in CAMR.